2013
DOI: 10.1007/s12275-013-3092-y
|View full text |Cite
|
Sign up to set email alerts
|

Free mycolic acid accumulation in the cell wall of the mce1 operon mutant strain of Mycobacterium tuberculosis

Abstract: The lipid-rich cell wall of Mycobacterium tuberculosis, the agent of tuberculosis, serves as an effective barrier against many chemotherapeutic agents and toxic host cell effector molecules, and it may contribute to the mechanism of persistence. Mycobacterium tuberculosis strains mutated in a 13-gene operon called mce1, which encodes a putative ABC lipid transporter, induce aberrant granulomatous response in mouse lungs. Because of the postulated role of the mce1 operon in lipid importation, we compared the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 39 publications
6
58
0
Order By: Relevance
“…Strikingly, most triple mutant Δ mlaE Δ pqiA Δ yebS cells exhibited cell surface ruffling, suggestive of gross disorganization of the OM, whereas the IM and OM of wild-type cells were smooth with a well-defined periplasm in between (Figures 1D, S1I, and S1J). This is consistent with results from Streptomyces coelicolor in which mutations in the single MCE gene cluster led to global changes in the cell surface (Clark et al, 2013), as well as other work suggesting that MCE mutants have altered OM lipid composition (Cantrell et al, 2013; Malinverni and Silhavy, 2009). Thus, MCE proteins are important for maintaining the morphology of the OM and the uniform spacing between the IM and OM.…”
Section: Resultssupporting
confidence: 91%
“…Strikingly, most triple mutant Δ mlaE Δ pqiA Δ yebS cells exhibited cell surface ruffling, suggestive of gross disorganization of the OM, whereas the IM and OM of wild-type cells were smooth with a well-defined periplasm in between (Figures 1D, S1I, and S1J). This is consistent with results from Streptomyces coelicolor in which mutations in the single MCE gene cluster led to global changes in the cell surface (Clark et al, 2013), as well as other work suggesting that MCE mutants have altered OM lipid composition (Cantrell et al, 2013; Malinverni and Silhavy, 2009). Thus, MCE proteins are important for maintaining the morphology of the OM and the uniform spacing between the IM and OM.…”
Section: Resultssupporting
confidence: 91%
“…Recently, Cantrell et al 19 and Ojha et al 20 reported that M. tuberculosis cell wall contains unattached MA (free MA or FM) (Figure 1). One potential source of FM is the hydrolysis of TDM.…”
Section: Trehalose Dimycolatementioning
confidence: 98%
“…M. tuberculosis has four homologs of mce operon (mce1-4) encoding ATP-binding cassette transporters (ABC transporters) possibly involved in lipid import 7,37,38 . Cantrell et al 19 and Forrellad et al 39 reported that disruption of mce1 operon results in a M. tuberculosis mutant that accumulates several-fold more FM in its cell wall than wild type bacteria. Both groups suggested that the operon might encode an importer system involved in recycling of MA.…”
Section: Mycolic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is one conflicting report, multiple studies show Mce1 (like SecA2) is important for growth in macrophages and during the early phase of murine infection (5-7, 67, 80 -83). The specific function of Mce1 during infection is not clear, but a potential role of Mce1 in importing free mycolic acids was recently proposed (57,84). Mce4 is the best studied Mce transporter, with a shown role in cholesterol import (85,86) and a role in virulence (85,87).…”
Section: Differences In Protein Families and Network In The ⌬Seca2mentioning
confidence: 99%